Evaluation of the Impact of the Wound Treatment Associate (WTA) Education Program on Practice and Quality Patient Outcomes. Issue 1 (January 2020) - Ramundo, Janet; Coverstone, Sara; Crumbley, David R.; Geiger, Donna; Jankowski, Irene; Ritter, Deborah; Smith, Shannon; Sutton, Angel
Abstract : PURPOSE: The Wound Treatment Associate (WTA) program is an education offering of the WOCN Society. This evidence-based continuing education program prepares nurses to serve as a unit-based resource for nursing staff. The WTA program is approved by the American Nurses Credentialing Association (ANCC) for 32.25 contact hours and aimed at licensed health care personnel. This article focuses on the impact of this education program, in particular a reduction in hospital-acquired pressure injury (HAPI) in acute care and decrease in visits per episode (VPE) and supply costs in home health. METHODS: Surveys were sent to all course participants to date to fulfill the summative evaluation requirement for ANCC approval to determine the perception of improvement in knowledge, skills, and practice. An additional survey was developed and reviewed by members to send to WTA program course coordinators. RESULTS: Participants (n = 153) reported an increase in confidence in knowledge and skills about wound care and use in nursing practice. The number of respondents to the course coordinator survey was lower (n = 48). Coordinators did report a reduction in pressure injuries in acute care. Home health respondents noted a decrease in VPE and reduction in the cost of supplies. Data reported on abstracts and posters suggested positive impacts of pressure injury prevention programs in acute and home health care. CONCLUSIONS: Although there are limitations to the aforementioned reporting, incorporating the WTA program into pressure injury prevention programs and wound treatment programs showed a reduction in HAPIs in acute care and decreased VPE and supply costs in home health.